Psychoanalysis, Anthropological Differences, and Political Forms: For an Intensive Difference - Sibertin-Blanc, Guillaume (Filozofski vestnik, 2017)
This article deals with the programme of a “topography” of the political subject: it is an attempt at writing the politics of “modernity” and the typical aporias inherent in its discursive regimes, in order to correlate the question of political subjectivation with the unconscious. Its purpose is not an “applied psychoanalysis”, nor a political psychology, but a problematisation of what repeats itself in politics, and what constitutes a “symptom” in such a repetition. Following Etienne Balibar’s analyses of the “proposition d’égaliberté” and the “three concepts of politics”, I attempt to articulate three components of the political modernity: the order of repetition, of which we have to understand the logics to catch its binding effect; the equivocity of the figures of the political subject, which is the main effect of this compulsion of repetition, but yet the only way to make it politically and subjectively productive; the contradiction between the universality of political discourse and its limit, a limit that politics confronts less as a border with its “extensive” other (as being “non-political”) than as the internal intensive differences putting politics into crisis (as being “impolitical”).